Aktivitas Antibakteri Kapang Endofit dari Tanaman Kina (Cinchona calisaya Wedd.) - Zakiyah, Alfida; Radiastuti, Nani; Sumarlin, La Ode (Al-Kauniyah: Jurnal Biologi, 2015)
Endophytic microorganisms are microorganisms that live in the tissues of plant organ and not harm its host. One of them is the endophytic fungi. Endophytic fungi could produce the same compound as the host plant. The Plants produced alkaloids quinine that could potentially inhibit the bacteria Staphylococcus aureus and Escherichia coli. This study aims to test the potential of endophytic fungi produced quinine as an antibacterial. The method used to test the antibacterial is a paper disc diffusion. Results of the analysis of data using one-way ANOVA showed that there are significant differences zona between the diametre of inhibitory of the endophytic fungi extract. Endophytic fungi M16 and M33 produced the greatest inhibition zone against Staphylococcus aureus and Escherichia coli 14.9 mm and 9.2 mm respectively.